2020
DOI: 10.1016/j.corsci.2020.109007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Cu content on corrosion, wear and tribocorrosion resistance of Ti-Mo-Cu alloy for load-bearing bone implants

Abstract: In this study, the effects of Cu content on wear, corrosion, and tribocorrosion resistance of Ti-10Mo-xCu alloy were investigated. Results revealed that hardness of Ti-10Mo-xCu alloy increased from 355.1±15.2 HV to 390.8±17.6 HV by increasing Cu content from 0% to 5%, much higher than CP Ti (106.6±15.1 HV) and comparable to Ti64 (389.7±13.9 HV). With a higher Cu content, wear and tribocorrosion resistance of Ti-10Mo-xCu alloys were enhanced, and corrosion resistance showed an initial increase with a subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Titanium alloys are chemically active and have high ductility, giving rise to a strong tendency for adhesion. 30 When the titanium alloy surface undergoes wear, it experiences severe deformation. Once the yield strength is surpassed, plastic deformation occurs on the material's surface and accumulates during repeated contact.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…Titanium alloys are chemically active and have high ductility, giving rise to a strong tendency for adhesion. 30 When the titanium alloy surface undergoes wear, it experiences severe deformation. Once the yield strength is surpassed, plastic deformation occurs on the material's surface and accumulates during repeated contact.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…In this paper, the root shape of the tooth was used as the study object, and the pore size should be greater than 300 μm, considering the need to promote the generation of new bone and capillaries [ 30 ]. Jetté et al, after analyzing the pore size through static testing (2018), suggested that the porosity should be between 40% and 70% when designing porous structures [ 13 ].…”
Section: Modelling and Finite Element Simulationmentioning
confidence: 99%
“…Density and hardness are two important properties that should be considered during assessing the wear and corrosion performances of metallic materials. [27][28][29] Thus, the density and hardness of CP-Ti fabricated using two different feedstocks and forged TC4 alloy were tested and evaluated first (Figure 2). It can be found that the relative density of all samples was higher than 99% and can be considered to close fully dense.…”
Section: Density Hardness and Microstructurementioning
confidence: 99%